FCC Physics Opportunities : Future Circular Collider Conceptual Design Report Volume 1 - Abada, A.; Zurita, J; Sjostrand, Torbjorn ; 0000-0002-7630-8605 (European Physical Journal C, 2019)
We review the physics opportunities of the Future Circular Collider, covering its e+e-, pp, ep and heavy ion programmes. We describe the measurement capabilities of each FCC component, addressing the study of electroweak, Higgs and strong interactions, the top quark and flavour, as well as phenomena beyond the Standard Model. We highlight the synergy and complementarity of the different colliders, which will contribute to a uniquely coherent and ambitious research programme, providing an unmatchable combination of precision and sensitivity to new physics.
Publisher Copyright: © 2019, The Author(s).